Electronic Correlations in Metalloproteins: a Quantum Monte Carlo Study - Mayda, Selma; Mayda, Selma; Bulut, Nejat (Izmir Institute of Technology, 2013)
Metalloproteins are proteins that contain a metal atom. Some metalloproteins include a transition metal such as vitamin B12 (Co) and hemoglobin (Fe) and these structures show semiconducting properties. In this thesis, as an example of metalloproteins, vitamin B12 is studied and electronic and magnetic properties of Co 3d electrons are examined by the quantum Monte Carlo method (QMC). Since vitamin B12 contains a cobalt (Co) atom and has a semiconductor gap, its electronic and magnetic properties can be described by multi-orbital Haldane-Anderson model. Haldane-Anderson model explains the electronic properties of semiconductors which contain a transition metal impurity and considers the onsite Coulomb interactions of impurity 3d orbitals. To solve this model, we use Hirsch-Fye quantum Monte Carlo algorithm (HFQMC) without making any approximations. Firstly, the occupations and intra-orbital electronic correlations of 3d orbitals are calculated. After that, the total magnetization and the inter-orbital correlations of 3d orbitals are obtained. Next, the total magnetic susceptibility and magnetic susceptibilities between the 3d orbitals are calculated. Finally, we discuss the physical meaning of the QMC calculations.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2013
Includes bibliographical references (leaves: 49-50)
Text in English; Abstract: Turkish and English
xiii, 91 leaves
Keywords: Monte Carlo method; Metalloproteins